Pengaruh Net Profit Margin (NPM) Dan Total Asset Turnover (TATO) Terhadap Pertumbuhan Laba Pada PT. Jembo Cable Company, Tbk - Khairunisa, Khairunisa; Huda, Nurul; Muthiah, Hanifah (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to determine and analyze the influence of Net Profit Margin (NPM) and Total Asset Turnover (TATO) on profit growth at PT. Jembo Cable Company, Tbk. This type of research is associative and comes from a research instrument in the form of a table listing sales, total assets and profit growth at PT. Jembo Cable Company, Tbk. The population in this research is all financial reports from PT. Jembo Cable Company, Tbk has been listed on the IDX since 1992 until 2022, namely for 32 years. The sample in this research is the financial report of PT. Jembo Cable Company, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research is purposive sampling. With the criteria (1) financial report data is available for 10 consecutive years, namely 2013-2022 (2) data The 10 year sample represents existing population data for research needs. Data collection in this research used documentation and literature study. The data that has been collected will be analyzed using the classical assumption test, multiple linear regression, multiple correlation coefficient, determination test, t test and f test.  The research results show that Net Profit Margin and Total Asset Turnover on profit growth have a positive and significant influence on PT. Jembo Cable Company, Tbk.